The Experience of Untapped Potential: Towards a Subjective Temporal Understanding of Work Meaningfulness - De Boeck, Giverny; Dries, Nicky; Tierens, Hans (Journal of Management Studies, 2019)
In this paper, we propose that untapped potential acts as a subjective temporal meaning‐making mechanism. Using a two‐wave survey design, we examine the relationship between job characteristics, untapped potential, and work meaningfulness in a heterogeneous sample of 542 employees. We found that employees’ perceived amount of untapped potential mediates the effects of skill variety, autonomy, and job feedback on work meaningfulness. This mediated relationship was moderated by the valence employees attributed to their untapped potential. Moreover, decreases in the perceived amount of untapped potential over time were related to increases in perceived work meaningfulness. Our research shows that work that allows employees to move beyond the here‐and‐now by providing opportunities to realize future work selves is experienced as particularly meaningful. We conclude that, if we wish to understand what makes work meaningful for employees in the present, we need to know how it aligns with their self‐perceptions in the future.